Polygenic risk for depression predicting temperament trajectories over 15 years: A general population study - Lavonius, Veikka (Elsevier, 2025)
Background A great number of case-control and population-based studies have shown that depression patients differ from healthy controls in their temperament traits. We investigated whether polygenic risk for depression predicts trajectories of temperament traits from early adulthood to middle age.
Methods Participants came from the population-based Young Finns Study (n = 2212). The calculation for Polygenic risk for depression (PRS) was based on the most recent genome-wide association study. Temperament traits of Harm Avoidance, Novelty Seeking, Reward Dependence, and Persistence were assessed with the Temperament and Character Inventory in 1997, 2001, 2007, and 2012 (participants being 24–50-year-olds). As covariates, we used depressive symptoms as assessed by a modified version of the Beck Depression Inventory, psychosocial family environment from parent-filled questionnaires, and socioeconomic factors from adulthood.
Results High PRS predicted higher Persistence from early adulthood to middle age (p = 0.003) when controlling for depressive symptoms, psychosocial family environment, and socioeconomic factors. PRS did not predict trajectories of Novelty Seeking (p = 0.063–0.416 in different models) or Reward Dependence (p = 0.531–0.736). The results remained unaffected when participants with diagnosed affective disorders were excluded. Additionally, we found an interaction between PRS and depressive symptoms when predicting the Harm Avoidance subscale Anticipatory Worry, indicating that the association of Anticipatory Worry with depressive symptoms is stronger in individuals with higher (vs. lower) PRS.
Limitations There was some attrition due to the long follow-up.
Conclusions High polygenic risk for major depression may predict differences in temperament trajectories among those who have not developed any severe affective disorders.